Acoustic improvement material with nano-micro-superstructure, preparation method of acoustic improvement material, loudspeaker and electronic equipment

By compounding silica aerogel reinforced with structurally reinforcing fillers and silicon-containing zeolite molecular sieves, a nano-superstructure acoustic improvement material with a regular microporous structure is formed, which solves the problem of clogging of small organic molecules and difficult pore distribution in existing porous materials. control issues and achieve better low-frequency acoustic effects.

CN119306510APending Publication Date: 2025-01-14SSI NEW MATERIAL (ZHENJIANG) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411390404.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The polymer adhesive introduced by existing porous materials during the molding process will cause small organic molecules to evaporate and be adsorbed, blocking the pore structure, causing acoustic performance to decline; at the same time, the pore distribution of amorphous materials is difficult to control, affecting the acoustic improvement effect.

Method used

Silica aerogel reinforced with structurally reinforcing fillers is combined with silicon-containing zeolite molecular sieves to form a nano-micro superstructure acoustic improvement material with a regular microporous structure through chemical bonding.

Benefits of technology

It achieves a more regular and stable pore structure of the acoustic improvement material, avoids the problem of clogging of small organic molecules, and improves the low-frequency acoustic effect of the speaker.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306510A_ABST
    Figure CN119306510A_ABST
Patent Text Reader

Abstract

The invention provides an acoustic improvement material with a nano-micro superstructure, a preparation method of the acoustic improvement material, a loudspeaker and electronic equipment, the acoustic improvement material with the nano-micro superstructure has micropores, mesopores and macropores at the same time, the acoustic improvement material with the nano-micro superstructure comprises silicon dioxide aerogel reinforced by a structure reinforcing filler and a silicon-containing zeolite molecular sieve, the silicon-containing zeolite molecular sieve is combined with the inside and the surface of the silicon dioxide aerogel reinforced by the structure reinforcing filler through chemical bonds. The acoustic improvement material with the nano-micro-superstructure provided by the invention has an excellent low-frequency acoustic improvement effect, relatively high strength, relatively low water absorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an acoustic improvement material with a nano-micro superstructure, a preparation method thereof, a loudspeaker and electronic equipment, and belongs to the technical field of materials, in particular to the technical field of electronic acoustic materials. Background Art

[0002] Miniaturization of speakers has become a mainstream trend and has attracted more and more attention. However, the acoustic quality of micro speakers deteriorates as the size decreases. Porous materials have a very high specific surface area and have a good adsorption-storage-desorption effect on air molecules. They are often used in micro speakers to improve low-frequency acoustic effects. When the speaker diaphragm vibrates, the pressure in the back cavity of the speaker changes, thereby compressing the air and allowing it to enter the porous material. When the pressure decreases, the air molecules adsorbed and stored in the porous material are released, thereby changing the rigidity of the air in the back cavity of the speaker and improving the low-frequency acoustic effect.

[0003] CN103098490A discloses a zeolite molecular sieve with a silicon-aluminum mass ratio of more than 200 as a speaker low-frequency improvement material, wherein the zeolite molecular sieve is formed into 0.2-0.9mm particles by an organic adhesive. The particles contain pore structures of different sizes and can achieve a good acoustic improvement effect; however, the introduction of organic adhesives will lead to the generation of volatile organic small molecules during long-term operation. If these organic small molecules cannot be discharged in time, they will be adsorbed by the zeolite molecular sieve in the particles, and part of the pore structure in the particles will be blocked, reducing its acoustic improvement effect.

[0004] CN109874089A discloses using SiO2 aerogel as a sound-absorbing material to improve the acoustic effect of a speaker; the sound-absorbing material contains pore structures such as mesopores and micropores. When a high molecular polymer binder is introduced, there is also the problem of organic volatile small molecules blocking the pore structure; in addition, SiO2 aerogel is an amorphous porous material, and the proportion of its micropores, mesopores, and macropores is difficult to control, and there is a lot of randomness in the synthesis process.

[0005] In summary, in the prior art, the polymer adhesive introduced into the porous material during the molding process will produce volatile organic small molecules during long-term operation. The organic small molecules are easily adsorbed by the porous material, blocking the pore structure and causing performance degradation; in addition, the pore distribution of amorphous materials is difficult to control.

[0006] Therefore, providing a new acoustic improvement material with nano-micro structure and its preparation method, loudspeaker, and electronic equipment has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0007] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide an acoustic improvement material having a nano-micro superstructure.

[0008] Another object of the present invention is to provide a method for preparing the acoustic improvement material having the nano-micro superstructure.

[0009] Another object of the present invention is to provide a speaker, wherein at least one of the speaker front cavity, speaker rear cavity, housing and sound-emitting unit is equipped with the above-mentioned acoustic improvement material with nano-micro structure.

[0010] Another object of the present invention is to provide an electronic device comprising the above-mentioned speaker.

[0011] In order to achieve the above objectives, on the one hand, the present invention provides an acoustic improvement material with a nano-micro superstructure, wherein the acoustic improvement material with a nano-micro superstructure has micropores, mesopores and macropores at the same time, and includes silica aerogel reinforced with a structure-reinforcing filler and a silicon-containing zeolite molecular sieve, and the silicon-containing zeolite molecular sieve is bonded to the interior and surface of the silica aerogel reinforced with the structure-reinforcing filler through chemical bonds (chemical bonds formed during the crystallization process).

[0012] As a specific embodiment of the acoustic improvement material described above, the mass ratio of the silicon-containing zeolite molecular sieve to the silica aerogel reinforced with the structural reinforcing filler is 1:2-1:4.

[0013] As a specific embodiment of the acoustic improvement material described above in the present invention, in order to ensure that the molecular sieve material has a strong bonding force with the silica aerogel reinforced with the structural reinforcing filler, the constituent elements of the molecular sieve must contain silicon, that is, the present invention must use a silicon-containing zeolite molecular sieve, wherein the silicon-containing zeolite molecular sieve includes a pure silicon structure molecular sieve, a silicon-aluminum structure molecular sieve, or a silicon-phosphorus-aluminum structure molecular sieve, etc.

[0014] The present invention does not impose any specific restriction on the silicon-aluminum ratio of the silicon-containing zeolite molecular sieve. Considering that the silicon-containing zeolite molecular sieve with a lower silicon-aluminum ratio has a good affinity for water molecules, in order to make the acoustic improvement material with a nano-micro structure have excellent resistance to water absorption, in practical applications, it can be considered to use a silicon-containing zeolite molecular sieve with a higher silicon-aluminum ratio (the molar ratio of silicon and aluminum atoms is not less than 100).

[0015] For silicon-aluminum structure molecular sieve, due to the requirement of structural electrical neutrality, cations outside the framework can be introduced, and the cations outside the framework can be one or a combination of hydrogen ions, monovalent metal ions, divalent metal ions and multivalent metal ions. The present invention does not make specific requirements on the method of introducing cations outside the framework of the silicon-aluminum structure molecular sieve, and the specific introduction method can be reasonably selected according to the actual operation needs on site and / or the specific substances of the cations, as long as it can ensure that the purpose of introducing cations outside the framework of the silicon-aluminum structure molecular sieve can be achieved.

[0016] As a specific embodiment of the acoustic improvement material described above, the total weight of SiO2 in the silica aerogel reinforced with the structural reinforcement filler is 100%, and the content of the structural reinforcement filler is 1-8%. Too high a content of the structural reinforcement filler will increase the water absorption rate of the acoustic improvement material with nano-micro superstructure, thereby affecting its acoustic performance.

[0017] As a specific embodiment of the acoustic improvement material described above, the silica aerogel reinforced with a structural reinforcement filler comprises a structural reinforcement filler and a silica aerogel, and the structural reinforcement filler is uniformly dispersed in the silica aerogel.

[0018] As a specific embodiment of the acoustic improvement material described above, the size of the silica aerogel reinforced with the structural reinforcing filler is 35-50 mesh.

[0019] As a specific embodiment of the acoustic improvement material described above in the present invention, the structural reinforcement filler includes one or a combination of halloysite, boehmite, mullite, glass fiber, expanded perlite and asbestos.

[0020] As a specific embodiment of the acoustic improvement material described above, the structure-reinforced filler is in the form of one or a combination of fibers, flakes, and nanotubes.

[0021] The present invention does not make specific requirements on the morphology of the acoustic improvement material with nano-micro superstructure. It can present different appearances according to the morphology of the silica aerogel reinforced by the structural reinforcement filler, and can select a suitable specific morphology according to the use requirements (such as the morphology of the rear cavity of the speaker). For example, its appearance can be an irregular morphology, such as one or a combination of irregular particles, irregular blocks, irregular sheets, irregular fibers and irregular polyhedrons, etc.; it can also be a regular morphology, such as one or a combination of regular spherical particles, nearly spherical regular particles, regular blocks, regular sheets and regular fibers, etc. In some embodiments, the large-sized acoustic improvement material with nano-micro superstructure can be formed by bonding the prepared nano-micro superstructure particles, that is, the smaller-sized acoustic improvement material with nano-micro superstructure.

[0022] On the other hand, the present invention also provides a method for preparing the acoustic improvement material having the nano-micro superstructure, wherein the preparation method comprises:

[0023] Dissolving a silicon source, an alkali source and a mineralizer in deionized water to obtain a molecular sieve mother liquor;

[0024] The silica aerogel reinforced with the structural reinforcing filler is added to the molecular sieve mother solution and mixed evenly, and then the obtained mixed solution is crystallized, and finally the crystallized product is washed, dried and calcined to obtain the acoustic improvement material with the nano-micro superstructure.

[0025] As a specific embodiment of the preparation method described above in the present invention, the molecular sieve mother liquor also contains a template. During the preparation of the molecular sieve mother liquor, an organic template may or may not be introduced, that is, the silicon-containing zeolite molecular sieve used in the present invention may be synthesized by a template method or a template-free method; the template-free method includes but is not limited to a seed induction method, etc. The silica aerogel reinforced with a structurally reinforced filler has good thermal stability, and the structure of the silica aerogel will not be destroyed even during the introduction of the template and the subsequent high-temperature burning of the template. The silicon-containing zeolite molecular sieve synthesized by the template-free method does not need to be calcined at high temperature to remove the template, thereby retaining the original pore structure.

[0026] As a specific embodiment of the preparation method described above, the calcination temperature is not higher than 700° C. In addition, the present invention does not make specific requirements on the specific materials and amounts of the silicon source, alkali source, mineralizer and template used in the preparation of the acoustic improvement material with nano-micro superstructure, and can be reasonably selected and adjusted according to the actual needs on site.

[0027] As a specific embodiment of the preparation method described above in the present invention, the preparation method of the silica aerogel reinforced with a structural reinforcing filler comprises:

[0028] A silicon source, a co-solvent and deionized water are mixed to obtain a first mixed solution, an acidic catalyst is added to the first mixed solution to hydrolyze the silicon source to produce a sol, a gel accelerator and a structure-reinforcing filler are then added to the sol and mixed evenly to obtain a second mixed solution, an alkaline catalyst is then added to the second mixed solution to form a wet gel, and finally the wet gel is aged and dried to obtain the silica aerogel reinforced with the structure-reinforcing filler.

[0029] As a specific embodiment of the preparation method described above in the present invention, the silicon source used in preparing the silica aerogel reinforced with structural reinforcing fillers is organic silicon and / or inorganic silicon, wherein the organic silicon includes one or a combination of tetraethyl orthosilicate (TEOS), methyl orthosilicate (TMOS), polysiloxane (PEDS), methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES) and silsesquioxane (POSS), and the inorganic silicon includes one or a combination of silica sol, water glass, sodium silicate and silicon tetrachloride.

[0030] As a specific embodiment of the preparation method described above in the present invention, the acid catalyst used in the preparation of the silica aerogel reinforced with a structural reinforcing filler is an organic acid catalyst and / or an inorganic acid catalyst, wherein the organic acid catalyst includes one or a combination of formic acid, acetic acid, oxalic acid, propionic acid, malonic acid, succinic acid, glutaric acid, citric acid, monosodium citrate, oleic acid and oxalic acid, and the inorganic acid catalyst includes one or a combination of hydrochloric acid, bromic acid, boric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, phosphoric acid, phosphorous acid, metaphosphorous acid, ammonium bisulfate, sodium bisulfate, potassium bisulfate, ferric acid and permanganic acid.

[0031] As a specific embodiment of the preparation method described above in the present invention, the alkaline catalyst used in the preparation of the silica aerogel reinforced with a structural reinforcing filler is an organic alkaline catalyst and / or an inorganic alkaline catalyst, wherein the organic alkaline catalyst includes one or a combination of methylamine, ethylamine, ethylenediamine, propylamine, propylenediamine, isopropylamine, diisopropylamine, butylamine, cyclohexylamine, hexamethylenediamine, melamine and imidazole, and the inorganic alkaline catalyst includes one or a combination of ammonia water, hydrazine hydrate, sodium bicarbonate, potassium bicarbonate, sodium carbonate, potassium carbonate, potassium oxalate, sodium oxalate, sodium formate and sodium acetate.

[0032] As a specific embodiment of the preparation method described above in the present invention, the cosolvent used in preparing the silica aerogel reinforced with structural reinforcing fillers includes one or a combination of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, butanol and butanediol.

[0033] As a specific embodiment of the preparation method described above of the present invention, the gel accelerator used in preparing the silica aerogel reinforced with structural reinforcing fillers includes one or a combination of formamide, acetamide, methylacetamide, methylenediformamide, terephthalamide and phthalamide.

[0034] As a specific embodiment of the preparation method described above of the present invention, when preparing the silica aerogel reinforced with a structural reinforcing filler, the temperature of the hydrolysis process is 40-80° C. and the time is 2-48 hours.

[0035] As a specific embodiment of the preparation method described above of the present invention, the crystallization temperature is 80-150° C. and the crystallization time is 12-72 h. Preferably, the crystallization temperature is 120° C. and the crystallization time is 48 h.

[0036] As shown above, the preparation method of the acoustic improvement material with nano-micro superstructure includes the preparation of silica aerogel reinforced with structural reinforcing fillers and the preparation of acoustic improvement materials with nano-micro superstructures, wherein the silica aerogel reinforced with structural reinforcing fillers is prepared by normal pressure drying method, and its preparation process generally includes the dissolution, hydrolysis, polycondensation, aging and drying of silicon source. In the early stage of the reaction, the silicon source is hydrolyzed to obtain the active monomer silicic acid, and a certain amount of structural reinforcing filler is added while stirring, and then the silicic acid is polycondensed to generate a polymer (sol) with silicon oxygen (-Si-O-Si-) as the main body, and then cross-linked to form a gel skeleton with a three-dimensional network structure. There are a large number of pores between the gel skeletons, which are filled with solvent molecules such as ethanol and water. The obtained wet gel is first aged, and then the liquid solvent in the gel is replaced by a gaseous substance through a drying process, thereby obtaining a silica aerogel reinforced with a structural reinforcing filler. In addition, when preparing silica aerogel reinforced with structural reinforcing fillers, the wet gel can be doped to improve its high temperature stability or the wet gel can be hydrophobically modified to increase its hydrophobicity as needed. The present invention does not make specific requirements on the specific operations of the doping process and the hydrophobic modification process, the process parameters used, and the doping substances and hydrophobic modifiers, which can be reasonably adjusted and selected according to actual needs.

[0037] In addition, according to the actual needs of the on-site operation, the silica aerogel reinforced with the structural reinforcing filler can be crushed and screened to obtain particles (such as particles with a size of 30-50 mesh), and then the obtained particles are placed in a polyurethane ball mill for rolling ball milling. The collision and friction between the particles are used to remove the sharp corners of the particles to obtain nearly spherical silica aerogel particles reinforced with the structural reinforcing filler for standby use. After ball milling, the appearance of the acoustic improvement material with nano-micro superstructure is a microsphere of suitable size, which does not require a subsequent molding process and can avoid the introduction of molding adhesives.

[0038] Then, silica aerogel reinforced with a structural reinforcing filler having an elemental composition similar to that of the molecular sieve is used as a crystallization carrier, which is immersed in a molecular sieve mother liquor containing a silicon source, an alkali source and a mineralizer, and stirred for a sufficiently long time so that the molecular sieve mother liquor can fully wet the silica aerogel; the molecular sieve mother liquor containing the silica aerogel is then transferred to a molecular sieve crystallization device, and appropriate crystallization conditions are set to carry out a crystallization reaction; after the reaction is completed, a microporous-mesoporous-macroporous nano-micro-metastructure acoustic material with regular micropore channels, i.e., the acoustic improvement material with a nano-micro-metastructure, can be obtained.

[0039] On the other hand, the present invention also provides a speaker, comprising one or more sound-emitting units and one or more shells, wherein the one or more sound-emitting units and the one or more shells are combined to form a speaker back cavity, wherein at least one of the speaker front cavity, speaker back cavity, shell and sound-emitting unit is equipped with the above-mentioned acoustic improvement material with nano-micro structure.

[0040] As a specific implementation of the above-mentioned loudspeaker of the present invention, the loudspeaker is a micro loudspeaker.

[0041] As a specific implementation of the loudspeaker described above in the present invention, the sound-emitting unit is an acoustic sensor or the like.

[0042] As a specific embodiment of the loudspeaker described above in the present invention, the acoustic improvement material with the nano-micro-metastructure can be loaded inside the rear cavity of the loudspeaker or adhered to the inner wall of the rear cavity of the loudspeaker; the acoustic improvement material with the nano-micro-metastructure can also be loaded inside the front cavity of the loudspeaker or adhered to the inner wall of the front cavity of the loudspeaker; the acoustic improvement material with the nano-micro-metastructure can also be adhered to the inner wall or outer wall of the shell; the acoustic improvement material with the nano-micro-metastructure can also be adhered to the back of the magnetic bowl of the sound unit and other positions.

[0043] In yet another aspect, the present invention further provides an electronic device, wherein the electronic device comprises the above-mentioned speaker.

[0044] As a specific embodiment of the electronic device described above in the present invention, the electronic device includes a smart phone, TWS earphones, headphones, smart glasses, smart watches, VR devices, AR devices, tablet computers or thin and light laptops, etc.

[0045] Compared with the prior art, the beneficial technical effects that can be achieved by the present invention include:

[0046] Compared with amorphous materials, silicon-containing zeolite molecular sieve is an inorganic microporous crystal structure with regular pore distribution. The present invention can introduce a regular microporous structure into amorphous porous materials such as aerogel by compounding the silicon-containing zeolite molecular sieve and the silica aerogel reinforced with a structural reinforcing filler, thereby forming a superstructure material with a microporous-mesoporous-macroporous nanostructure with regular micropores, that is, the acoustic improvement material with a nano-micro superstructure provided by the present invention combines the regular microporous structure of the silicon-containing zeolite molecular sieve with the mesoporous and macroporous structures of SiO2 aerogel and the advantages of light weight.

[0047] The acoustic improvement material with nano-micro superstructure provided by the present invention has pore structures of three scale levels: macropores, mesopores, and micropores. The presence of these pores makes the nano-micro superstructure material have a very large specific surface area. Compared with non-porous materials, these pores can provide a larger area and more sites for the adsorption of air molecules. In the acoustic improvement material, the pores of the macropores are generally larger than 50nm, the size of the mesopores is between 2-50nm, and the size of the micropores is less than 2nm; and the size of the molecules in the air is all below 1nm, therefore, the macropores and large-sized mesopores in the acoustic improvement material can allow air molecules to freely enter the pore structure, while the micropores and small-sized mesopores will affect the free diffusion of air molecules. In the process of air molecule diffusion, it is inevitable that they come into contact with the atoms constituting the pore wall and are adsorbed. When the speaker diaphragm vibrates, the diaphragm is compressed inward, which increases the pressure in the rear cavity of the speaker, thereby changing the movement state of air molecules, causing them to quickly enter the porous material, increasing the probability of contact between air molecules and the pore walls, and causing the air molecules to be adsorbed; when the diaphragm vibrates outward, the pressure in the rear cavity of the speaker decreases, and the adsorbed air molecules leave the pore walls due to the pressure difference, changing from an adsorbed state to a desorbed state, and diffuse into large pores or large-sized mesopores; the vibration of the diaphragm causes the pressure in the rear cavity of the speaker to change, thereby causing the state of air molecules in the acoustic improvement material to continuously change, that is, the state change process is diffusion-adsorption-desorption-diffusion, thereby changing the rigidity of the air in the rear cavity of the speaker, thereby achieving the effect of improving the low-frequency acoustic effect.

[0048] In addition, the acoustic improvement material with a nano-micro superstructure provided by the present invention contains silica aerogel reinforced with a structural reinforcing filler. The introduction of the structural reinforcing filler enhances the structural strength of the SiO2 aerogel. Moreover, when preparing the acoustic improvement material with a nano-micro superstructure, the present invention does not require a subsequent molding process, and can avoid introducing a molding adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0050] Figure 1 This is a scanning electron microscope image of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 of the present invention.

[0051] Figure 2 This is a scanning electron microscope image of the acoustic improvement material with nano-micro structure prepared in Example 1 of the present invention.

[0052] Figure 3 This is a scanning electron microscope image of the Z-5 molecular sieve seed crystal used in Example 2 of the present invention.

[0053] Figure 4 This is a scanning electron microscope image of the acoustic improvement material prepared in Comparative Example 1.

[0054] Figure 5 This is a micro-mesopore distribution diagram of the acoustic improvement material with nano-micro superstructure prepared in Example 1 of the present invention.

[0055] Figure 6 This is a mesopore distribution diagram of the acoustic improvement material with nano-micro superstructure prepared in Example 1 of the present invention.

[0056] Figure 7 This is a macropore distribution diagram of the acoustic improvement material with nano-micro superstructure prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0057] It should be noted that the term "comprises" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0058] "Scope" disclosed in the present invention is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a specific parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0059] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in the present invention, and "0-5" is just an abbreviation of these numerical combinations.

[0060] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.

[0061] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.

[0062] In the present invention, unless otherwise specified, all steps mentioned herein may be performed sequentially or randomly, but are preferably performed sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0063] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the attached table, drawings and examples. The following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0064] Preparation Example 1

[0065] This preparation example provides a halloysite fiber reinforced silica aerogel microsphere, which is prepared by a preparation method comprising the following specific steps:

[0066] Take tetraethyl orthosilicate as silicon source, deionized water as solvent, anhydrous ethanol as cosolvent (to increase the solubility of tetraethyl orthosilicate in deionized water), oxalic acid as acid catalyst, ammonia water as alkaline catalyst and formamide as gel promoter. First, weigh deionized water, anhydrous ethanol and tetraethyl orthosilicate in order according to the molar ratio of 10:5:1 and mix them, transfer the mixed solution to a 45°C water bath, add 0.1M oxalic acid solution dropwise during stirring until pH=2, and stir for 30 minutes. During this process, tetraethyl orthosilicate is hydrolyzed to produce sol; then add formamide dropwise, the molar ratio of formamide to tetraethyl orthosilicate is 0.7:1, stir for 5-10 minutes while adding formamide, add 3wt% of halloysite fiber with a length of 800nm-1.2μm (the amount is calculated based on the SiO2 content in tetraethyl orthosilicate) during stirring and mix them evenly, wherein halloysite is a kind of aluminum oxide. The aluminosilicate material composed of and silicon oxide has high thermal stability and corrosion resistance; fibrous halloysite is added to the mother liquor used to prepare silica aerogel, and it can participate in the sol-gel process of silica aerogel; then, a 0.5M ammonia solution is added until the pH is 7, and after stirring evenly, it is allowed to stand to produce gel, and a wet gel can be obtained when the liquid surface does not flow at an angle of 45°; a 50v% ethanol solution is added to the wet gel, and the liquid level is higher than the wet gel, and the wet gel is aged for 24h; finally, the aged wet gel is staged dried, that is, first dried at 60°C for 4h and then dried at 80°C for 8h, to obtain a silica aerogel reinforced with halloysite fibers.

[0067] The prepared halloysite fiber reinforced silica aerogel is crushed into fine particles; the crushed particles are screened with a sieve to obtain microparticles with a size of 30-40 mesh; the particles are then transferred to a polyimide ball mill for ball milling, and the friction and collision between the particles are used to remove the irregular edges of the particles to obtain ellipsoidal or spherical particles; finally, the particles are screened again to obtain approximately spherical halloysite fiber reinforced silica aerogel particles / microparticles with a size of 35-50 mesh, and are placed in a room temperature dryer for use.

[0068] Preparation Example 2

[0069] This preparation example provides a 35-50 mesh size halloysite fiber reinforced silica aerogel microsphere, and the preparation method thereof differs from the preparation method in Preparation Example 1 only in that:

[0070] 10% of halloysite fibers were introduced.

[0071] Comparative Preparation Example 1

[0072] This comparative preparation example provides an unreinforced silica aerogel microsphere with a size of 35-50 mesh, and the preparation method thereof differs from the preparation method in Preparation Example 1 only in that:

[0073] Halloysite fibers were not introduced.

[0074] Example 1

[0075] This embodiment provides an acoustic improvement material having a nano-micro superstructure, which is prepared by a preparation method comprising the following specific steps:

[0076] Silica sol (SiO2 accounting for 30wt%) is used as the silicon source, sodium aluminate is used as the aluminum source, sodium hydroxide is used as the alkali source and mineralizer, and deionized water is used as the solvent;

[0077] The specific preparation process is as follows: weigh 0.103g of sodium aluminate and dissolve it in 91.0g of deionized water, then add 2.5g of NaOH, and stir rapidly at room temperature for 10min to obtain solution A; slowly add solution A to 100.0g of the above silica sol. During the addition of solution A, attention should be paid to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol, the stirring speed is reduced; continue stirring at room temperature for 1.0h to obtain a mixed solution; then add 53.25g of tetrapropylammonium bromide to the above mixed solution, and stir at room temperature for 0.5h to complete the preparation of the molecular sieve mother solution;

[0078] Subsequently, 8.0 g of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 were added to the molecular sieve mother liquor, and stirring was continued for 1 hour. The resulting mixed solution was then transferred to a PTFE-lined reactor and crystallized at 120°C for 48 hours. After the crystallization was completed, the resulting crystallized product was centrifuged and washed several times to obtain a nano-micro superstructure acoustic material, which was then dried overnight at 100°C and then calcined at 550°C for 6 hours to obtain a nano-micro superstructure acoustic material with the template removed, i.e., the acoustic improvement material with a nano-micro superstructure. According to the mass change of the material before and after crystallization, the mass ratio of the crystallized molecular sieve, i.e., the silicon-containing zeolite molecular sieve, to the halloysite fiber-reinforced silica aerogel microspheres was 1:3.

[0079] Example 2

[0080] This embodiment provides an acoustic improvement material having a nano-micro superstructure, which is prepared by a preparation method comprising the following specific steps:

[0081] Silica sol (SiO2 accounting for 30wt%) is used as the silicon source, sodium aluminate is used as the aluminum source, sodium hydroxide is used as the alkali source and mineralizer, and deionized water is used as the solvent;

[0082] The specific preparation process is as follows: weigh 0.103g of sodium aluminate and dissolve it in 91.0g of deionized water, then add 2.5g of NaOH, and stir rapidly at room temperature for 10min to obtain solution A; slowly add solution A to 100.0g of the above silica sol. During the addition of solution A, attention should be paid to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol, the stirring speed is reduced; continue stirring at room temperature for 1.0h to obtain a mixed solution; then add 1.5g of nano-sized Z-5 molecular sieve as a seed crystal to the above mixed solution, and stir at room temperature for 0.5h to complete the preparation of the molecular sieve mother solution;

[0083] Subsequently, 8.0 g of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 were added to the molecular sieve mother liquor, and stirring was continued for 1 hour. The resulting mixed solution was then transferred to a PTFE-lined reactor and crystallized at 120°C for 48 hours. After the crystallization was completed, the resulting crystallized product was centrifuged and washed several times to obtain a nano-micro superstructure acoustic material, and then dried overnight at 100°C to obtain the acoustic improvement material with a nano-micro superstructure. According to the mass change of the material before and after crystallization, the mass ratio of the crystallized molecular sieve, i.e., the silicon-containing zeolite molecular sieve, to the halloysite fiber-reinforced silica aerogel microspheres was 1:3.1.

[0084] Example 3

[0085] This embodiment provides an acoustic improvement material having a nano-micro superstructure, which is prepared by a preparation method comprising the following specific steps:

[0086] Silica sol (SiO2 accounting for 30wt%) is used as the silicon source, sodium aluminate is used as the aluminum source, sodium hydroxide is used as the alkali source and mineralizer, and deionized water is used as the solvent;

[0087] The specific preparation process is as follows: weigh 0.103g of sodium aluminate and dissolve it in 91.0g of deionized water, then add 2.5g of NaOH, and stir rapidly at room temperature for 10min to obtain solution A; slowly add solution A to 100.0g of the above silica sol. During the addition of solution A, attention should be paid to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol, the stirring speed is reduced; continue stirring at room temperature for 1.0h to obtain a mixed solution; then add 1.5g of nano-sized Z-5 molecular sieve as a seed crystal to the above mixed solution, and stir at room temperature for 0.5h to complete the preparation of the molecular sieve mother solution;

[0088] Subsequently, 8.0 g of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 2 were added to the molecular sieve mother liquor, and stirring was continued for 1 hour. The resulting mixed solution was then transferred to a PTFE-lined reactor and crystallized at a constant temperature of 120°C for 48 hours. After the crystallization was completed, the resulting crystallized product was centrifuged and washed several times to obtain a nano-micro superstructure acoustic material, and then dried overnight at a temperature of 100°C to obtain the acoustic improvement material with a nano-micro superstructure. According to the mass change of the material before and after crystallization, the mass ratio of the crystallized molecular sieve, i.e., the silicon-containing zeolite molecular sieve and the halloysite fiber-reinforced silica aerogel microspheres was 1:3.2.

[0089] Comparative Example 1

[0090] This comparative example provides an acoustic improvement material, which is prepared by a preparation method comprising the following specific steps:

[0091] Silica sol (SiO2 accounting for 30wt%) is used as the silicon source, sodium aluminate is used as the aluminum source, sodium hydroxide is used as the alkali source and mineralizer, and deionized water is used as the solvent;

[0092] The specific preparation process is as follows: weigh 0.103g of sodium aluminate and dissolve it in 91.0g of deionized water, then add 2.5g of NaOH, and stir rapidly at room temperature for 10min to obtain solution A; slowly add solution A to 100.0g of the above silica sol. During the addition of solution A, pay attention to adjusting the stirring speed. When a colloidal substance is found in the experiment, the stirring speed should be increased accordingly. When the solution is formed into a sol-like state, the stirring speed should be reduced; continue stirring at room temperature for 1.0h to obtain a mixture. solution; then, 53.25 g of tetrapropylammonium bromide was added to the mixed solution, and the mixture was stirred at room temperature for 0.5 h to complete the preparation of the molecular sieve mother solution; then, the obtained molecular sieve mother solution was transferred to a PTFE-lined reactor and crystallized at a constant temperature of 120°C for 48 h; after the crystallization, the obtained crystallized product was centrifuged and washed several times, and then dried at 100°C overnight, and then calcined at 550°C for 6 h to obtain the molecular sieve powder material with the template removed, that is, the acoustic improvement material.

[0093] Characterization Test Example 1

[0094] In this characterization test example, the halloysite fiber reinforced silica aerogel microspheres prepared in Preparation Example 1, the acoustic improvement material with nano-microstructure prepared in Example 1, the Z-5 molecular sieve seeds used in Example 2, and the acoustic improvement material prepared in Comparative Example 1 were analyzed by scanning electron microscope. The experimental results are shown as follows: Figure 1-Figure 4 As shown. Among them, Figure 1 This is a scanning electron microscope image of the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1. Figure 1 It can be seen that after ball milling, the particles have nearly spherical appearance and the particle size is about 300 μm; Figure 2 This is a scanning electron microscope image of the acoustic improvement material with nano-micro superstructure prepared in Example 1. When preparing the material, the silica aerogel microspheres reinforced by halloysite fibers are used as carriers, and the silicon-containing zeolite molecular sieve is crystallized on the inner and outer surfaces of the carrier. After crystallization, the surface of the silica aerogel particles reinforced by the halloysite fibers becomes somewhat rough, and the particle size increases. Figure 3 It can be seen that the Z-5 molecular sieve seeds are in the shape of round cakes, and the seed size is 300nm; the acoustic improvement material of Comparative Example 1 does not introduce aerogel microspheres during the preparation process, and the obtained particles are pure molecular sieve particles, with a size of 1μm. Figure 4 shown.

[0095] Characterization Test Example 2

[0096] This characterization test example investigates the pore size distribution of the acoustic improvement material with nano-microstructure prepared in Example 1. The obtained micro-mesopore distribution diagram, mesopore distribution diagram and macropore distribution diagram are shown as follows: Figure 5 , Figure 6and Figure 7 As shown. Figure 5 and Figure 6 It can be seen from the figure that the acoustic improvement material has micro-mesopores, the size of which is between 0.6-1.25nm, with the largest distribution of 0.75nm; the mesopores are mostly distributed at 2.1nm and 3.1nm; Figure 7 It can be seen that the acoustic improvement material also has macropores within 100 μm, but most of the macropores are within 50 μm.

[0097] Performance Test Example 1

[0098] In this embodiment, the strength of the halloysite fiber reinforced silica aerogel particles prepared in Preparation Example 1-Preparation Example 2, the acoustic improvement materials with nano-micro superstructures prepared in Example 1-Example 3, and the unreinforced silica aerogel microspheres prepared in Comparative Preparation Example 1 were tested in accordance with the provisions of Standard T / CECA 78-2022 "Porous Sound-Absorbing Particles for Micro Speakers". The strength test results are shown in Table 1 below.

[0099] Table 1

[0100] Particle strength / N Preparation Example 1 0.102 Preparation Example 2 0.123 Comparative Preparation Example 1 0.075 Example 1 0.126 Example 2 0.123 Example 3 0.127

[0101] According to the strength test results shown in Table 1 above, compared with the unreinforced (i.e., no reinforcing fiber introduced) silica aerogel microspheres prepared in Comparative Preparation Example 1, the silica aerogel microspheres reinforced with halloysite fibers prepared in Preparation Example 1 have higher particle strength. Increasing the content of halloysite fibers will improve the particle strength of the silica aerogel microspheres to a certain extent. Specifically, the microspheres provided in Preparation Example 2 are silica aerogel microspheres reinforced with 10%wt of halloysite fibers, which also have stronger particle strength than Comparative Preparation Example 1 and Preparation Example 1. After the silicon-containing molecular sieve is crystallized on the surface and inside of the silica aerogel microspheres reinforced with halloysite fibers, the particle strength of the final acoustic improvement material will also be improved; compared with the acoustic improvement material with a nano-micro superstructure prepared by the seed crystal method in Example 2 of the present invention, the acoustic improvement material with a nano-micro superstructure prepared by the template method in Example 1, the crystallized silicon-containing molecular sieve requires high-temperature calcination to remove the template agent in the pores. During the high-temperature calcination process, the halloysite fibers and the silica aerogel particles can be further fused, thereby improving the particle strength of the overall material. Compared with the acoustic improvement material with a nano-micro superstructure prepared by the seed crystal method in Example 2 of the present invention, the acoustic improvement material with a nano-micro superstructure prepared by the template method in Example 1 has a slightly higher particle strength. Example 3: Based on the halloysite fiber reinforced silica aerogel microspheres provided in Preparation Example 2, an acoustic improvement material with a nano-micro superstructure is prepared by a seed crystal method. Compared with the halloysite fiber reinforced silica aerogel microspheres provided in Preparation Example 2, the particle strength of the acoustic improvement material with a nano-micro superstructure is improved, that is, after the silicon-containing molecular sieve is crystallized on the surface and inside of the halloysite fiber reinforced silica aerogel microspheres, the particle strength of the final acoustic improvement material is improved.

[0102] Performance Test Example 2

[0103] In this embodiment, the water absorption rates of the halloysite fiber reinforced silica aerogel particles prepared in Preparation Examples 1-2, the acoustic improvement materials with nano-microstructures prepared in Examples 1-3, the unreinforced silica aerogel microspheres prepared in Comparative Preparation Example 1, and the acoustic improvement materials prepared in Comparative Example 1 were tested in accordance with the provisions of Standard T / CECA 78-2022 "Porous Sound-Absorbing Particles for Micro Speakers". The water absorption test results are shown in Table 2 below.

[0104] Table 2

[0105] M1 / g M2 / g Water absorption / % Preparation Example 1 2.001 2.018 0.85 Preparation Example 2 2.001 2.037 1.80 Comparative Preparation Example 1 2.001 2.017 0.80 Example 1 2.001 2.015 0.70 Example 2 2.000 2.014 0.70 Example 3 2.001 2.032 1.35 Comparative Example 1 2.002 2.012 0.50

[0106] According to the water absorption test results shown in Table 2 above, it can be seen that the silica aerogel microspheres reinforced with an appropriate amount of halloysite fibers (Preparation Example 1), the unreinforced silica aerogel microspheres (Comparative Preparation Example 1) and the silica aerogel microspheres reinforced with an excess of halloysite fibers (Preparation Example 2) all have high water absorption. This is mainly because the presence of silanol groups in the silica aerogel gives it a high water absorption rate. At the same time, halloysite is a material with a low silicon-aluminum ratio and is also a material with a good affinity for water. Therefore, the excessive introduction of halloysite will lead to a significant increase in the overall water absorption of the material.

[0107] Since the acoustic improvement materials provided in Examples 1 to 3 include halloysite fiber-reinforced silica aerogel microspheres and silicon-containing zeolite molecular sieves, the silicon-containing zeolite molecular sieves are chemically bonded to the interior and surface of the halloysite fiber-reinforced silica aerogel microspheres, and the silicon-containing zeolite molecular sieves have good hydrophobicity, the water absorption rates of the acoustic improvement materials provided in Examples 1 to 2 are lower than those of the halloysite fiber-reinforced silica aerogel microspheres provided in Preparation Example 1, and the water absorption rate of the acoustic improvement material provided in Example 3 is also correspondingly lower than that of the halloysite fiber-reinforced silica aerogel microspheres provided in Preparation Example 2.

[0108] From the water absorption data of the acoustic improvement materials provided by Comparative Examples 1 to 3, it can be seen that due to the higher water absorption of the silica aerogel microspheres reinforced with excess halloysite fibers provided in Preparation Example 2, the water absorption of the acoustic improvement material provided by Example 3 is also significantly higher than that of the acoustic improvement materials of Examples 1 and 2.

[0109] Performance Test Example 3

[0110] In this embodiment, the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Examples 1-2, the acoustic improvement materials with nano-micro structures prepared in Examples 1-3, the unreinforced silica aerogel microspheres prepared in Comparative Preparation Example 1, and the acoustic improvement materials prepared in Comparative Example 1 were respectively filled into a standard sound cavity (the volume of the sound cavity was 1.0 cubic centimeters, the specific structure of the sound cavity can be referred to CN215072984U, and the filling amount of the sound-absorbing material to be tested was 300 mg), and then the acoustic performance tests were performed on them respectively, wherein the acoustic The performance test is carried out by conventional methods in the art. For example, the acoustic performance of each sample to be tested is tested by referring to the "Measurement of Electrical Impedance" method shown in paragraphs 0049-0054 of Chinese patent application CN105049997A. Specifically, each sample to be tested is tested according to the "Measurement of Electrical Impedance" method to obtain an electrical impedance spectrum. The curve in the electrical impedance spectrum corresponds to the electrical impedance curve, wherein the frequency corresponding to the highest point of the electrical impedance curve is F0. When the sample to be tested is not loaded in the speaker, the measured F0 is marked as F0-空腔 When the speaker is loaded with each sample to be tested, the measured F0 is marked as F 0-待测样品 , then the calculation formula of ΔF0 is:

[0111] ΔF0=F 0-空腔 -F 0-待测样品 .

[0112] The test signal used in the acoustic performance test process is the analog program signal or pink noise signal specified in GB / T 12060.1.

[0113] The test results obtained in this embodiment are shown in Table 3.

[0114] Table 3

[0115]

[0116]

[0117] According to the acoustic performance test results shown in Table 3 above, the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1 can achieve a certain low-frequency acoustic improvement effect. Compared with the halloysite fiber-reinforced silica aerogel microspheres prepared in Preparation Example 1, when the halloysite fiber is not introduced as a reinforcing filler, the low-frequency acoustic improvement effect of the silica aerogel microspheres is not improved in Comparative Preparation Example 1. Preparation Example 2 introduces an excessive amount of halloysite fiber reinforcing filler, and the low-frequency acoustic improvement effect of the halloysite fiber-reinforced silica aerogel microspheres obtained therefrom is slightly decreased compared with Preparation Example 1 and Comparative Preparation Example 1.

[0118] Compared with the halloysite fiber reinforced silica aerogel microspheres prepared in Preparation Examples 1-2 and the silica aerogel microspheres prepared in Comparative Preparation Example 1, the acoustic improvement material prepared in Comparative Example 1 using only molecular sieve powder has an improved low-frequency acoustic improvement effect.

[0119] Compared with the acoustic improvement material prepared in Comparative Example 1, in Examples 1 to 3 of the present invention, the nano-micro superstructure material with micropores-mesopores-macropores obtained after the molecular sieve mother solution is crystallized on the surface and inside of the halloysite fiber-reinforced silica aerogel microspheres, that is, the acoustic improvement material with a nano-micro superstructure has excellent low-frequency acoustic improvement effect. However, Example 3 uses an excessive amount of halloysite fiber-reinforced silica aerogel microspheres and prepares the nano-micro superstructure acoustic improvement material by the seed crystal method. Compared with Examples 1 to 2, the low-frequency acoustic improvement effect of the nano-micro superstructure acoustic improvement material provided by Example 3 is reduced, which indicates that the introduction of excessive halloysite fiber-reinforced fillers will slightly reduce the low-frequency acoustic improvement effect of the obtained nano-micro superstructure acoustic improvement material.

[0120] It can also be seen from Table 3 that the nano-micro meta-structure materials crystallized by the template method and the template-free method in Example 1 and Example 2 of the present invention, that is, the acoustic improvement materials with nano-micro meta-structures, have no obvious difference in low-frequency improvement effect.

[0121] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. An acoustic improvement material having a nano-micro superstructure, characterized in that: The acoustic improvement material with nano-micro superstructure has micropores, mesopores and macropores at the same time, and includes silica aerogel reinforced with structure-reinforced fillers and silicon-containing zeolite molecular sieves, wherein the silicon-containing zeolite molecular sieves are chemically bonded to the interior and surface of the silica aerogel reinforced with structure-reinforced fillers.

2. The acoustic improvement material according to claim 1, characterized in that: The mass ratio of the silicon-containing zeolite molecular sieve to the silica aerogel reinforced with a structural reinforcing filler is 1:2-1:

4.

3. The acoustic improvement material according to claim 1 or 2, characterized in that: The silicon-containing zeolite molecular sieve includes a pure silicon structure molecular sieve, a silicon-aluminum structure molecular sieve or a silicon-phosphorus-aluminum structure molecular sieve.

4. The acoustic improvement material according to claim 1, characterized in that: Taking the total weight of SiO2 in the silica aerogel reinforced with the structural reinforcing filler as 100%, the content of the structural reinforcing filler is 1-8%.

5. The acoustic improvement material according to claim 1 or 4, characterized in that: The silica aerogel reinforced with a structural reinforcing filler comprises a structural reinforcing filler and a silica aerogel, wherein the structural reinforcing filler is uniformly dispersed in the silica aerogel.

6. The acoustic improvement material according to claim 1 or 4, characterized in that: The size of the silica aerogel reinforced with the structural reinforcing filler is 35-50 mesh.

7. The acoustic improvement material according to claim 1 or 2, characterized in that: The structural reinforcement filler includes one or a combination of halloysite, boehmite, mullite, glass fiber, expanded perlite and asbestos.

8. The acoustic improvement material according to claim 7, characterized in that: The structure-reinforced filler may be in the form of one or a combination of fibers, flakes and nanotubes.

9. The method for preparing the acoustic improvement material having a nano-micro superstructure according to any one of claims 1 to 8, characterized in that: The preparation method comprises: Dissolving a silicon source, an alkali source and a mineralizer in deionized water to obtain a molecular sieve mother liquor; The silica aerogel reinforced with the structural reinforcing filler is added to the molecular sieve mother solution and mixed evenly, and then the obtained mixed solution is crystallized, and finally the crystallized product is washed, dried and calcined to obtain the acoustic improvement material with the nano-micro superstructure.

10. The preparation method according to claim 9, characterized in that: The molecular sieve mother solution also contains a template.

11. The preparation method according to claim 9 or 10, characterized in that: The method for preparing the silica aerogel reinforced with a structural reinforcing filler comprises: A silicon source, a co-solvent and deionized water are mixed to obtain a first mixed solution, an acidic catalyst is added to the first mixed solution to hydrolyze the silicon source to produce a sol, a gel accelerator and a structure-reinforcing filler are then added to the sol and mixed evenly to obtain a second mixed solution, an alkaline catalyst is then added to the second mixed solution to form a wet gel, and finally the wet gel is aged and dried to obtain the silica aerogel reinforced with the structure-reinforcing filler.

12. The preparation method according to claim 11, characterized in that: The silicon source is organic silicon and / or inorganic silicon, wherein the organic silicon includes one or a combination of ethyl orthosilicate, methyl orthosilicate, polysiloxane, methyltrimethoxysilane, methyltriethoxysilane and silsesquioxane, and the inorganic silicon includes one or a combination of silica sol, water glass, sodium silicate and silicon tetrachloride.

13. The preparation method according to claim 9 or 10, characterized in that: The crystallization temperature is 80-150° C., and the crystallization time is 12-72 hours. Preferably, the crystallization temperature is 120° C., and the crystallization time is 48 hours.

14. A speaker, comprising one or more sound-emitting units and one or more shells, wherein the one or more sound-emitting units and the one or more shells are combined to form a speaker rear cavity, characterized in that: At least one of the speaker front cavity, speaker rear cavity, housing and sound generating unit is equipped with the acoustic improvement material with nano-micro superstructure as claimed in any one of claims 1 to 8.

15. The loudspeaker according to claim 14, characterized in that The speaker is a micro speaker.

16. An electronic device, characterized in that: The electronic device comprises the speaker according to claim 14 or 15.

17. The electronic device according to claim 16, characterized in that: The electronic device includes a smart phone, a TWS headset, a head-mounted headset, smart glasses, a smart watch, a VR device, an AR device, a tablet computer or a thin and light laptop computer.

Citation Information

Patent Citations

  • Loudspeaker system with improved sound

    CN103098490A

  • Loudspeaker System with Improved Sound

    CN105049997A

  • A silicon dioxide aerogel sound absorption material and a sound production device

    CN109874089A

  • Acoustic material testing tool assembly

    CN215072984U